Molecular characterization of Streptococcus pneumoniae, particularly serotype19A/ST320, which emerged in Krasnoyarsk, Russia. (September 2017) - Protasova, Irina N.; Wan, Tsai‐Wen; Bakhareva, Natalya V.; Hung, Wei‐Chun; Higuchi, Wataru; Iwao, Yasuhisa; Yelistratova, Tatyana A.; Ilyenkova, Natalya A.; Sokolovskaya, Yelena S.; Martynova, Galina P.; Reva, Ivan V.; Reva, Galina V.; et al.
ABSTRACT: Streptococcus pneumoniae, a common human pathogen, colonizes the nasopharynx and causes diseases including acute otitis media (AOM). Herein, pneumococcal serotype distributions in children before and after PCV7 vaccination and in patients with pneumococcal disease in Siberian Russia (Krasnoyarsk) are reported. Analyses included antimicrobial susceptibility testing, sequence typing (ST), pulsed field gel electrophoresis, virulence‐related surface protein gene (VSG) typing with novel primers and structural analysis by scanning electron microscopy. In healthy children (HC) prior to administration of PCV7, drug‐susceptible serotype23F/ST1500 was a major pneumococcal genotype. In the PCV7 trial, multidrug‐resistant serotype19A/ST320 emerged in vaccinees after PCV7, exhibiting a PCV7‐induced serotype replacement. Multidrug‐resistant serotype19A/ST320 was evident in patients with AOM. Community‐acquired pneumonia (CAP) isolates showed genetic similarities to the AOM (ST320) genotype, constituting a common non‐invasive AOM–CAP group. In contrast, meningitis isolates were more divergent. Overall, 25 ST types were identified; five (20%) of which were Krasnoyarsk‐native. Regarding VSGs, PI‐1 ( rlrA / rrgB ), PI‐2 ( pitA / B ), psrP and cbpA were present at 54.3%, 38.6%, 48.6%, and 95.7%, respectively, with two major VSG content types, PI‐1 − /PI‐2 − / psrP + / cbpA + and PI‐1 + /PI‐2 + / psrP ‐ / cbpA +, being found for HC and non‐invasive diseases, respectively. A major clone of serotype19A/ST320 (PI‐1 + /PI‐2 + ) produced the longest pneumococcal wire (pilus) structures in colonies. ST1016 (PI‐1 − /PI‐2 − ) in HC had HEp‐2 cell‐adherent pili. These results suggest that serotype19A/ST320 and related genotypes, with the VSG content type PI‐1 + /PI‐2 + / psrP − / cbpA +, emerged in vaccinees after PCV7 in Siberia, accompanying diseases in non‐vaccinated children, and that some genotypes (serotypes19A/ST320 and 18/ST1016) produced novel pneumococcal structures, predicting their roles in colony formation and adherence.